Prehistoric Pottery Sources And Technology In Peninsular Malaysia Based On Compositional And Morphological Studies - Chia, Stephen Ming Soon (1992)
This study attempts to identify prehistoric pottery sources in order to locate areas of prehistoric pottery production in Peninsular Malaysia. The identification of pottery production areas can help resolve the issue of the origins of the "Black Ware" from Bukit Tengku Lembu, which was said to have had foreign origins. The compositional approach, used here in pottery studies for the first time in Malaysia, was combined with the traditional morphological approach to study a total of ninety-seven pottery sherds. These samples were obtained from the sites of Bukit Tengku Lembu, Kodiang, Gua Cha, the Lenggong cave massifs, Gua Kecil, Gua Sagu, and Jenderam Hilir.